Tradisi Bancakkan dan Ruwahan sebagai Wujud Integrasi Islam dan Budaya Jawa - Pramuditya, Agatha Prahista (Javano Islamicus, 2026)
The Bancakkan and Ruwahan traditions represent the integration of Islamic teachings and Javanese culture in community life. The presence of Islam in Java did not eliminate local traditions; rather, it interacted dialogically with them, giving rise to religious practices that are contextual and deeply rooted in everyday life. The Bancakkan and Ruwahan traditions serve as concrete examples of this acculturation process, in which Islamic values such as prayer, almsgiving, gratitude, and togetherness are expressed through Javanese cultural symbols and rituals. This study aims to examine the religious, social, and cultural meanings embedded in these traditions, as well as to explain their role in shaping a moderate and harmonious pattern of Javanese religiosity. This research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings indicate that the Bancakkan and Ruwahan traditions function not only as religious rituals but also as means of strengthening social solidarity, maintaining social bonds, and preparing the spiritual condition of the community prior to the month of Ramadan. Therefore, local traditions make an important contribution to maintaining a balance between religious values and cultural practices in Javanese society.